Pemanfaatan Organ Tumbuhan sebagai Obat yang Diolah secara Tradisional di Desa Wukirsari Kecamatan Tugumulyo Kabupaten Musi Rawas - Nopa Nopiyanti; Andung Eliska; Intan Nuryani; Yuli Febrianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Traditional medicinal plants are ingredients or natural ingredients derived from plants that have been used for generations for treatment based on experience. The use of plants as medicine has been around for a long time. Knowledge of medicinal plants is a national heritage based on experiences that have been passed down from generation to generation. Inheritance of knowledge about traditional medicine from generation to generation in society is the cause of the extinction of this knowledge. The knowledge possessed by traditional communities in the village is rarely written down, mostly only known by those who are old. Meanwhile, the younger generation, especially those who have integrated into modern life, rarely care about the knowledge that society has. This study aims to collect information from the public regarding the use of plant organs as traditional medicine in Wukirsari Village, Tugumulyo District, Musi Rawas Regency. This research is a descriptive study using interviews, observation, and literature studies. From the research results, it was found that the types of plants that have been used as medicinal plants in Wukirsari village, Tugumulyo district, Musirawas district totaled 17 species from 13 families and the parts of the plants used were 46.6% leaves, 26.6% rhizomes, 16.6% fruit, and 10% bark/stem. Keywords: Traditional Medicine, Utilization, Medicinal Plants